Hands-On Design Patterns with Java Learn Design Patterns That Enable the Building of Large-Scale Software Architectures. - Lavieri, Edward (Packt Publishing, Limited, 2019)
Software design is informed by proven patterns and approaches. Several software design patterns have been established and documented to inform the process. Java design patterns are proven solutions and approaches to programming problems. This book covers over 60 design patterns along with implementation details, using latest version of Java.